Volumetric and mechanical properties of bituminous concrete mixes with the addition of polyethylene terephthalate - Mukesh Saini; Praveen Aggarwal; Sameer Algburi; Abdullah Faiz Al Asmari; Parveen Berwal (Case Studies in Construction Materials, 2025)
Waste plastics, littered both by domestic and industrial sectors, have been identified as a potential source of raw material for flexible pavements. Hence, understanding the behavior of bituminous mixes incorporating plastic is crucial for effective pavement design. There is limited information about the properties of modified mixes containing waste plastic bottles made of polyethylene terephthalate (PET). In this study, the effects of PET on the volumetric and mechanical properties of bituminous concrete mixes were analyzed. Using a dry process, these characteristics were examined with different proportions of PET (ranging from 0 % to 14 % by weight of bitumen, in 2 % increments). The results demonstrate that the mechanical and volumetric properties of the bituminous mixes improved significantly, with the optimum PET content found to be 8 %. Incorporating PET into bituminous mixes is not only a sustainable and economical way to manage plastic waste, but it also enhances the performance of bituminous materials.